2003
DOI: 10.1093/oxfordjournals.schbul.a007038
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Cascade and Schizophrenia: Etiology and Onset

Abstract: Psychosocial stress is included in most etiologic models of schizophrenia, frequently as a precipitating factor for psychosis in vulnerable individuals. Nonetheless, the stress-diathesis model has not been tested prospectively in prodromal patients as a predictor of psychosis. The biological effects of stress are mediated by the hypothalamic-pituitary-adrenal (HPA) axis, which governs the release of steroids, including cortisol. The past few decades have witnessed an increased understanding of the neural effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
235
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(259 citation statements)
references
References 201 publications
(203 reference statements)
10
235
0
2
Order By: Relevance
“…In particular, evidence suggests that early life stress is an important factor in the etiology of schizophrenia, a developmental disorder that typically manifests in adolescence or early adulthood. Stressful life events can precipitate or exacerbate the psychotic symptoms of schizophrenia (Corcoran et al, 2003;Meyer-Lindenberg and Tost, 2012) and psychosocial stressors increase the risk for developing the disease (Lim and Chong, 2009). It has been suggested that individuals who are at risk for schizophrenia are more susceptible to the effects of stress and that the interaction between a genetic or developmental predisposition and stress in early life could promote symptom onset (Benes, 1997;Tsuang, 2000;Walker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, evidence suggests that early life stress is an important factor in the etiology of schizophrenia, a developmental disorder that typically manifests in adolescence or early adulthood. Stressful life events can precipitate or exacerbate the psychotic symptoms of schizophrenia (Corcoran et al, 2003;Meyer-Lindenberg and Tost, 2012) and psychosocial stressors increase the risk for developing the disease (Lim and Chong, 2009). It has been suggested that individuals who are at risk for schizophrenia are more susceptible to the effects of stress and that the interaction between a genetic or developmental predisposition and stress in early life could promote symptom onset (Benes, 1997;Tsuang, 2000;Walker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A third possible explanation is that environmental factors might predispose to altered trajectory of brain development, but individual genetic susceptibility defines the phenotype (and ultimately the diagnosis). We favor this last explanation (Horvath and Mirnics, 2014b), as MIA and immune system activation predispose to both autism and schizophrenia (Michel et al, 2012;Patterson, 2009), and early stress predisposes to a host of psychiatric disorders (Chrousos and Gold, 1992;Corcoran et al, 2003;O'Donnell, 2012;Walker et al, 2008). However, symptoms of autism emerge very early in life while schizophrenia onset is typically during late adolescence or early adulthood.…”
Section: Future Research Directionsmentioning
confidence: 94%
“…Previous research has shown that the psychosocial environment may have a negative influence on the course o f schizophrenia, particularly on acute wards (Concoran et al, 2003;, where patients experience many relationships (Forster et ah, 2003), there is a high staff turnover , and staff work many different shifts . Conversely, a supportive ward environment is considered by many as a precondition for successful treatment (Schalast, Redies, Collins, Stacey & Howells, 2008) and research has highlighted that situational stressors that exacerbate symptoms of schizophrenia can be lessened through a supportive environment .…”
Section: Ward Atmosphere and Psychosismentioning
confidence: 99%